On the approximation of the classes W_β^rH^α by biharmonic Poisson integrals - Hrabova, U. Z.; Kalchuk, I. V.; Stepanyuk, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain asymptotic equalities for the least upper bounds of the deviations of biharmonic Poisson integrals from functions of the classes W_β^rH^α in the case where r > 2, 0 ≤ α < 1.